High Peak‐Current Lightning Discharges Associated With Downward Terrestrial Gamma‐Ray Flashes. Issue 4 (13th February 2020) - Wada, Y.; Enoto, T.; Nakamura, Y.; Morimoto, T.; Sato, M.; Ushio, T.; Nakazawa, K.; Yuasa, T.; Yonetoku, D.; Sawano, T.; Kamogawa, M.; Sakai, H.; et al.
Abstract: During 2017–2018 winter operation of the Gamma‐Ray Observation of Winter Thunderclouds experiment in Japan, two downward terrestrial gamma‐ray flashes (TGFs) that triggered atmospheric photonuclear reactions were detected. They took place during winter thunderstorms on 5 December 2017 and 9 January 2018 at Kanazawa, Ishikawa Prefecture, Japan. Each event coincided with an intracloud/intercloud discharge, which had a negative‐polarity peak current higher than 150 kA. Their radio waveforms in the low‐frequency band are categorized as a distinct lightning type called "energetic in‐cloud pulse" (EIP). Negative‐polarity EIPs have been previously suggested to be highly associated with downward TGFs, and the present observations provide evidence of the correlation between them for the first time. Furthermore, both of the downward TGFs followed "gamma‐ray glows, " minute‐lasting high‐energy emissions from thunderclouds. It is suggested that the negative EIPs took place with downward propagating negative leaders or upward positive ones developed in highly electrified regions responsible for the gamma‐ray glows. Plain Language Summary: We observed, on the ground, intense and brief gamma‐ray emissions, called "downward terrestrial gamma‐ray flashes, " twice during winter thunderstorms in Japan. They coincided with a kind of in‐cloud lightning discharges called "negative energetic in‐cloud pulses." They have been previously predicted to have a connection to downward terrestrial gamma‐ray flashes, and we observationally confirm the prediction for the first time. Furthermore, the two downward terrestrial gamma‐ray flashes were preceded by weak and minute‐lasting gamma‐ray emissions coming from thunderclouds, called "gamma‐ray glows." High electric fields inside thunderclouds required to produce gamma‐ray glows were thus related to the downward terrestrial gamma‐ray flashes and the negative energetic in‐cloud pulses. Key Points: Two downward terrestrial gamma‐ray flashes detected in Japan were coincident with high peak‐current lightning discharges The lightning discharges can be categorized as negative energetic in‐cloud pulses Both cases took place in highly electrified regions responsible for production of gamma‐ray glows